Robot Layanan Publik Robot Layanan Publik Di Politeknik Negeri Manado - Feyhrel Fayen Makahekung; Rivaldi Musa; Ruth Natasia Chingyi Rares; Marson James Budiman (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
The development of incrasingliy sophisticated technology and rapid industrial growth in Indonesia.robot technology is also developing significantly over time. Therefore technology is very useful and important in today’s industrial era, which can facilitate human work. The development of the robot is not only in the sophistication of its mechanical design, but also its control system using a computerized system. Along with the development of robotic development techniques, it is increasingly easier for humans to make tobots tha have intelligence that follows the will and will of huimans themselves. With the Public Service Robot, it can help break the chain of Covid-19 spread on the Manado State Polytechnic campus, such as students an alumni who take files in the administrative basement of the central building, robots can deliver and retrieve files so that employees and students do not make physical contact directly. Immediately, the Robot that will be created is called the Public Service Robot. System for Robot Control using Arduino Microcontroller. Keywords: Public Service, Arduino, File Delivery Robot